Potentials of Plantation Timbers in Improving Rural Economy - Mishra, Manika; Mishra, Harendranath (Indian Forester, 1995)
Methodology of achieving success in Social Forestry Schemes has been discussed. The strategy calls for collection, preservation and sawing in time the improved variety of seeds of some selected fast growing forestry species including Eucalyptus, selection of suitable land depending on its geoclimatic factors to grow high yielding trees to produce, in shorter rotation, adequate fodder, fruit, fuelwood and constructional timbers, technique of using Eucalyptus in low cost house building, maximising the benefits to the weaker sections of the society by providing them employment opportunities to improve the rural economy to a great extent.